2014
DOI: 10.3748/wjg.v20.i40.14652
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic disease: Liver and beyond

Abstract: The harmful use of alcohol is a worldwide problem. It has been estimated that alcohol abuse represents the world's third largest risk factor for disease and disability; it is a causal factor of 60 types of diseases and injuries and a concurrent cause of at least 200 others. Liver is the main organ responsible for metabolizing ethanol, thus it has been considered for long time the major victim of the harmful use of alcohol. Ethanol and its bioactive products, acetaldehyde-acetate, fatty acid ethanol esters, eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
147
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(155 citation statements)
references
References 68 publications
1
147
0
7
Order By: Relevance
“…Alcoholic abuse initiates or increases susceptibility to many related diseases and is therefore a major public health problem worldwide. 116 The gut plays a role in alcohol-related diseases, both directly, through alcohol absorption and alteration of the intestinal barrier, and indirectly, through the microbiota-mediated transformation of alcohol into toxic compounds (e.g., acetaldehyde) and alcohol-induced dysbiosis. 116,117 Alcohol stimulated iHSP25 at concentrations between 10 and 40 g/L and iHSP70 at 10 g/L, with a loss of iHSP responses at higher concentrations (80 g/L) in Caco2 cells.…”
Section: Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholic abuse initiates or increases susceptibility to many related diseases and is therefore a major public health problem worldwide. 116 The gut plays a role in alcohol-related diseases, both directly, through alcohol absorption and alteration of the intestinal barrier, and indirectly, through the microbiota-mediated transformation of alcohol into toxic compounds (e.g., acetaldehyde) and alcohol-induced dysbiosis. 116,117 Alcohol stimulated iHSP25 at concentrations between 10 and 40 g/L and iHSP70 at 10 g/L, with a loss of iHSP responses at higher concentrations (80 g/L) in Caco2 cells.…”
Section: Other Diseasesmentioning
confidence: 99%
“…116 The gut plays a role in alcohol-related diseases, both directly, through alcohol absorption and alteration of the intestinal barrier, and indirectly, through the microbiota-mediated transformation of alcohol into toxic compounds (e.g., acetaldehyde) and alcohol-induced dysbiosis. 116,117 Alcohol stimulated iHSP25 at concentrations between 10 and 40 g/L and iHSP70 at 10 g/L, with a loss of iHSP responses at higher concentrations (80 g/L) in Caco2 cells. 118 Importantly, another study reported that alcohol (60 g/L) moderately stimulated the expression of HSF1 and iHSP70, but this was not protective.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Damage to the stomach in alcoholics differs from damage to other organs, such as the liver, because ethanol consumption affects the upper gastrointestinal tract through multiple and complex mechanisms. These mechanisms depend on contact with ethanol that can cause direct mucosal damage (Franke et al 2005) or nonalcoholic components (e.g., fermentation products) (Rocco et al 2014). Thus, alcoholism is considered an independent risk factor for the initiation and complications associated with ulcerative disease, similar to smoking, stress, Helicobacter pylori infection, and the chronic use of nonsteroidal anti-inflammatory drugs (NSAIDs) (Birdane et al 2007;Galuska et al 2002;Gisbert and Pajares 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the qualitative analysis, the following parameters were analyzed for the nucleus and cytoplasm of hepatocytes: area, perimeter, maximum and minimum diameter and form factor. Six photos were taken of each fragment in 400 fields, 3 photos of the portal region and 3 photos of the central region, since fat accumulation initially occur in zone 3 (perivenular) of hepatocytes and, with the progression of steatosis, it reaches zones 2 and 1 (periportal) [1,2,[11][12][13]. In each photo, 10 nuclei and 10 cytoplasm tissues were analyzed.…”
Section: Histopathological Examination Of the Livermentioning
confidence: 99%